JEAN-JACQUES DESSALINES, THE SAVAGE THE QUESTION OF HISTORICAL MINIMIZATION - Déus, Frantz Rousseau; Logis, Berno [UNESP] (Pontifical Catholic University of Sao Paulo (PUC-SP), 2024)
The purpose of this article is to discuss, through a bibliographic review, the way Jean-Jacques Dessalines — one of the important Black revolutionaries from the late 18th to early 19th centuries — is portrayed in the dominant historiography of that time. Largely minimized in hegemonic historiography, Dessalines is depicted in a contemptible manner. The French historian Louis Dubroca characterizes him as a barbarian, essentially cruel, and an ‘enemy of European culture and values.’This way of representing Dessalines is related both to the place of power in the production of history and to what we call historical minimization, which would be a process of reducing to a minimum the importance and value of important figures in historiography in general, whether for reasons of race, whether due to gender. The figure of the leader of the Haitian revolution of 1791-1804 was minimized because he belonged to a group of human beings that Euro-American science and philosophy considered to be racially inferior.
JEAN-JACQUES DESSALINES, “O SELVAGEM” A QUESTÃO DA MINIMIZAÇÃO HISTÓRICA
Keywords: dominant historiography; Jean-Jacques Dessalines; Historical minimization; racism